NEW MEDIA, NEW LANGUAGE: LINGUOSTYLISTIC TRANSFORMATION IN SOCIAL NETWORKS - Alua Kakharmanova (Modern Scientific Technology, 2025)
As digital platforms evolve, so does the language used within them. This paper analyzes the linguostylistic shifts occurring on social networks, focusing on the hybridization of oral and written speech. By examining 2025 trends such as "Algospeak," visual syntax, and punctuation-based affect, the study concludes that New Media is not degrading language but optimizing it for high-velocity, globalized interaction